2020
DOI: 10.1097/ccm.0000000000004268
|View full text |Cite
|
Sign up to set email alerts
|

Mean Airway Pressure As a Predictor of 90-Day Mortality in Mechanically Ventilated Patients*

Abstract: Objectives: To determine the association between mean airway pressure and 90-day mortality in patients with acute respiratory failure requiring mechanical ventilation and to compare the predictive ability of mean airway pressure compared with inspiratory plateau pressure and driving pressure. Design: Prospective observational cohort. Setting: Five ICUs in Lima, Peru. Subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…It may be consistent with those from previous studies showing that early use NIV is associated with a significant reduction of post-extubation respiratory failure [19,25]. However, this finding must be validated in further prospective studies [14][15][16][17][18]21].…”
Section: Prospective Validation and A Web-based Toolsupporting
confidence: 89%
See 1 more Smart Citation
“…It may be consistent with those from previous studies showing that early use NIV is associated with a significant reduction of post-extubation respiratory failure [19,25]. However, this finding must be validated in further prospective studies [14][15][16][17][18]21].…”
Section: Prospective Validation and A Web-based Toolsupporting
confidence: 89%
“…Pressure of oxygen in blood (PaO 2 ) means the tension created by the oxygen physically dissolving in the blood, which is assessed during blood gas analysis. Mean airway pressure (Pmean), showed on the ventilator, determined by the peak inspiratory pressure (PIP), PEEP, and the inspiratory to expiratory time ratio [ 15 ]. The mean airway pressure was measured for NIV within 6 h of initiation.…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, Pmean is a potential indicator of lung stress. A recent multicenter study showed that in a group of mechanically ventilated ARDS patients, Pmean was independently associated with 90-day mortality and correlated with Pplat or Pdriv, which had predicted mortality like the implication of Pplat or Pdriv [8] . From this point of view, Pmean also has potential prompt significance when spontaneous breathing is too strong or breathing drive is too high.…”
mentioning
confidence: 99%
“…The critical values associated with intensive care mortality for various pressures and mechanical power parameters (P mean ; 17 cmH 2 O, P peak ; 26 cmH 2 O, ΔP insp ; 15 cmH 2 O, PEEP; 9.3 cmH 2 O, MP tot ; 17 j/min) were found to align with previously published studies, supporting the clinical relevance of these thresholds. 21,[43][44][45] Notably, patients who remained in the prone position for more than 15.5 h per day exhibited a lower rate of intensive care mortality. This observation corresponds with findings from other investigations, which have reported reduced mortality rates in patients who spent more than 16 h per day in the prone position.…”
Section: Discussionmentioning
confidence: 99%